Non-O1/O139 environmental Vibrio cholerae from Northern Cameroon reveals potential intra-/inter-continental transmissions. - Deborah Yebon Kang; Mohammad Tarequl Islam; Roméo Wakayansam Bouba; Zoua Wadoubé; Moussa Djaouda; Yann Felix Boucher (PLoS Neglected Tropical Diseases)
Northern Cameroon in Central Africa has experienced recurring cholera outbreaks despite ongoing efforts to control the disease. While most cholera studies focus on O1 pandemic Vibrio cholerae strains, non-O1/O139 strains are increasingly recognized for their infection potential and dynamic relationships with O1 strains during outbreaks. Here we explore the genetic diversity and phylogenetic relationships of non-O1/O139 V. cholerae (NOVC) isolated from environmental water sources in Northern Cameroon. These NOVC strains show significant genetic diversity and virulence potential. They are closely related to environmental strains from Kenya and clinical strains from Argentina and Haiti, suggesting transmissions across countries and continents, likely facilitated by human carriers. The highly conserved tcpA gene found in some strains from Cameroon is closely related to the tcpA O1 Classical type, suggesting direct or indirect genetic interactions between these environmental NOVC strains and pandemic strains. Our findings underscore the importance of environmental surveillance and further studies of NOVC strains to better understand cholera outbreaks.